2020
DOI: 10.3390/polym12092064
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activated Carbon Nanofibers Composited with Cost-Effective Graphene-Based Materials for Enhanced Adsorption Performance toward Methane

Abstract: Various types of activated carbon nanofibers’ (ACNFs) composites have been extensively studied and reported recently due to their extraordinary properties and applications. This study reports the fabrication and assessments of ACNFs incorporated with graphene-based materials, known as gACNFs, via simple electrospinning and subsequent physical activation process. TGA analysis proved graphene-derived rice husk ashes (GRHA)/ACNFs possess twice the carbon yield and thermally stable properties compared to other sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Othman et al [91] also reported 66.40 mmol g À1 of CH 4 adsorption by graphene (derived from rice husk ashes) and carbon nanofiber composites prepared by electrospinning. Dou et al [92] reported CH 4 storage capacity of Cu-ion-modified MOF dispersed in PAN nanofiber (86 cm 3 g À1 ) and 3500 kPa.…”
Section: Adsorption Of Methane Carbon Dioxide Acetone and Other Gases...mentioning
confidence: 97%
See 1 more Smart Citation
“…Othman et al [91] also reported 66.40 mmol g À1 of CH 4 adsorption by graphene (derived from rice husk ashes) and carbon nanofiber composites prepared by electrospinning. Dou et al [92] reported CH 4 storage capacity of Cu-ion-modified MOF dispersed in PAN nanofiber (86 cm 3 g À1 ) and 3500 kPa.…”
Section: Adsorption Of Methane Carbon Dioxide Acetone and Other Gases...mentioning
confidence: 97%
“…Methane storage properties of carbon nanofibers modified with magnesium oxide (MgO) and manganese dioxide (MnO 2 ) were studied by Othman et al [ 90 ] They reported maximum CH 4 adsorption up to 2.39 mmol g −1 by MgO‐modified PAN nanofiber. Othman et al [ 91 ] also reported 66.40 mmol g −1 of CH 4 adsorption by graphene (derived from rice husk ashes) and carbon nanofiber composites prepared by electrospinning. Dou et al [ 92 ] reported CH 4 storage capacity of Cu‐ion‐modified MOF dispersed in PAN nanofiber (86 cm 3 g −1 ) and 3500 kPa.…”
Section: Electrospun Nanofibers For Gas Storage Applicationsmentioning
confidence: 99%
“…Figure 7 simply summarizes the top view structure of the spinnerets. Fibers with complex nanostructures can be prepared through multifluid electrospinning and can be used in different fields, such as drug release [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ], tissue engineering [ 100 ], lithium battery energy storage [ 101 , 102 ], antibacterial [ 103 , 104 ] and environmental remediation [ 105 , 106 ]. However, only few studies focused on the use of multifluid electrospinning to prepare functional fiber membranes for water treatment applications.…”
Section: Electrospinningmentioning
confidence: 99%
“…These interlinked micropores and mesopores are responsible for gas adsorption as reported by Durá et al [113] GRHA200 exhibited the largest SSA of 1556.3 m 2 /g and TPV of 1.1269 cm 3 /g, with the largest micro-pore volume distribution of 0.5782 cm 3 /g. Othman et al [114] demonstrated the synthesis of activated carbon nanofibers (ACNFs) incorporated with graphene-based materials called gACNFs. GRHA/ACNFs exhibited the highest SSA, of 384 m 2 /g, with ahigh micro-pore volume of 0.1580 cm 3 /g, which is up to 88% of the total pore volume.…”
Section: Gas Storagementioning
confidence: 99%